Wider economic benefits from communication cost reductions: an endogenous growth approach - Johannes Bröcker (European Regional Science Association (ERSA), 2012)
The paper examines the impact of communication cost reductions on growth and welfare by means of an endogenous spatial growth model. Policy makers having to decide upon transport policies often claim certain policies such as infrastructure investments to have growth stimulating effects that generate "wider impacts" in terms of welfare, well beyond producer and consumer surplus effects typically measured by traditional cost-benefit analysis. It is well understood that such wider impacts cannot arise in a first-best environment with perfect competition and no externality. If the market allocation is however not first-best wider effects in general do occur and can in principle have both signs. As far as freight costs are concerned, existence of wider effects has been shown in the literature in a static NEG framework. Huge infrastructure projects such as high-speed trains have however no direct freight cost effect, but are nevertheless conjectured to generate wider impacts. The typical argument is that innovation needs face to face contact and generates positive externalities. Thus, cheaper contacts boost growth and generate benefits of the society as a whole beyond those that the users are privately willing to pay for. To verify these claims rigorously I set up a Romer-type endogenous growth model for a multiregional economy. In this model innovators need to learn from the existing stock of knowledge by communicating with others across space, which is a costly activity. I show that, at the margin, reducing these costs generates a welfare gain that consumers value more then the cost reduction itself.
Keywords: D61; O18; O33; R13; R48; 330